Interv'iu s khudozhnikom Evgeniem Orlovym . Interv'iu s khudozhnikom Evgeniem Orlovym . Interview With Artist Evgenii Orlov . Интервью с художником Евгением Орловым - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Talk with the painter Evgenii Orlov. Featured in the program: Orlov, Evgenii (Painter) Беседа с художником Евгением Орловым. В программе участвуют: Орлов, Евгений (Художник)